Utilization Of Papaya Leaf (Carica Papaya) Infusion As A Natural Anesthesia In Stone Lobster (Panulirus Penicillatus) - Yanti, Riska Dwi; Ukhty, Nabila; Fuandi, Afdhal; Amri, Chairul (Jurnal Fish Protech, 2023)
Lobster is a fishery product that has export value. In the export stage, lobsters are usually transported using the wet system transportation method or the dry system transportation method. The dry system transportation method to reduce lobster metabolism and respiration during transportation is separation. One of the natural ingredients that can be used is papaya leaf infusion. The aims of this study were to determine the effect of papaya leaf infusion as a natural anesthetic agent on rock lobsters, and to determine the best concentration of papaya leaf infusion as a natural anesthetic agent for rock lobsters. This study used an experimental method with 3 treatments and 3 replications, the study used a completely randomized design (CRD) with treatment concentrations P1: 100gram/L, P2: 150gram/L and, P3: 200gram/L. The data collected included inductive time, sedative time, and survival rate of the lobsters. The data obtained were analyzed statistically and quantitatively descriptively, statistical analysis using IBM SPSS Statistics 25 with the ANOVA test and the Significant Difference Test (BNJ). The results of the ANOVA test showed that giving water infisum of papaya leaves (Carica papaya) to rock lobster (Panulirus Penicillatus) with different concentrations had an effect (P<0.05) on inductive time but had no effect (P>0.05) on sedative time. Further tests using the Honest Significant Difference (BNJ) test showed that the concentrations of P1 and P2 were significantly different from P3. The survival rate is relatively high, namely P1 100%, P2 100%, and P3 77.33%. The best concentration of papaya leaf infisum as a natural anesthetic for rock lobsters is treatment P1 with a concentration of 100 grams/L which can stun lobsters in 50 minutes 16 seconds, 2 minutes of conscious (sedative) time, and a very high survival rate of 100%.